Application of Artificial Intelligence in Banking and Finance : Bibliometric Review and Emerging Research Agenda - Gujrati, Priyanka; Biradar, Jivan (Indian Journal of Computer Science, 2023)
Artificial Intelligence (AI) has been growing at the fastest pace during the last few decades. It has affected all sectors directly or indirectly. The application of AI is getting more mature with the passage of time and the banking sector is adopting it intensively. Existing literature in the subject is scattered across all regions of the world. The purpose of this study is to understand major contributions of researchers, subject experts, and the sources along with countries that are actively involved in the area of research. To do the bibliometric study, systematic review of 756 documents published from 1972 to 2021 in Scopus database has been used as it is the largest of all databases available. With this bibliometric analysis, it was found that the USA, China, UK, India, and Taiwan have been the major countries in making extra efforts continuously for unfolding the new possibilities of Artificial Intelligence in the banking and finance sector.